Hydropower rent in Africa : An evaluation by optimization of the total costs of production - (:unkn) unknown (My University, 2020)
The main goal of this study is to estimate the potential economic rent generated in the African hydropower sector. To this end, the methodology used is to calculate the rent as the difference between optimized total costs of two hypothetical systems: one with hy-dropower and the other without hydropower. Of course, our results depend on a number of key parameters of the electricity industry. Our calculation gives a value of 2 $/MWh of hydropower rent. Thus, developing hydropower in Africa would help the continent to en-sure its energy transition. This exploitation does not only provide surplus return for coun-tries with significant potential, but it is also a source of revenue for all other hydropower importing countries. This calls for joint implementation of projects.
Keywords: African Research